Government Spending, Unemployment, and Islamic Human Development Index: Evidence from Indonesia and Malaysia - Tirtayudha, Muhammad Fiqhi; Darwanto (Jurnal Ekonomi Syariah Teori dan Terapan, 2025)
This study aims to analyse the effect of government spending and unemployment on the Islamic Human Development Index (IHDI) in Indonesia and Malaysia during the period 2013-2022. This study uses panel data regression method with Common Effect approach to test the relationship between these variables. The results of the analysis show that both government spending and unemployment have a negative and significant influence on the IHDI partially. This finding indicates that government spending, when not managed effectively, can actually hinder the achievement of human development goals in an Islamic perspective. Similarly, high levels of unemployment reduce the ability of individuals to fulfil basic needs which contributes to a decline in the quality of life and well-being of the society. In conclusion, more efficient budget management and unemployment reduction efforts are important factors in improving IHDI in Indonesia and Malaysia.